2016
DOI: 10.20435/1984-042x-2016-v.17-n.4(12)
|View full text |Cite
|
Sign up to set email alerts
|

São os Arranjos Produtivos Locais apoiados capazes de afetar a renda dos municípios do estado do Rio Grande do Sul?

Abstract: Este artigo avaliou o impacto dos incentivos públicos aos Arranjos Produtivos Locais - APLs sobre o PIB per capita dos municípios do Rio Grande do Sul. Após a identificação dos APLs, aplicou-se a metodologia de MQO e de Estimação de Diferenças em Diferenças para captar o efeito do apoio ao APL sobre o PIB per capita. Na análise de APLs selecionados, apenas o APL de máquinas e implementos agrícolas apresentou impacto positivo sobre o PIB per capita com significância estatística.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Although there are several studies on clusters impact evaluation on local development (MARINI; SILVA; NASCIMENTO, 2016; OLIVERIA; SANTANA, 2016; OLIVEIRA; MARTINELLI, 2014; MACEDO; DIAZ MERINO; DALLAZEN CAMILLO, 2014), most of them are case studies or qualitative studies. Studies based on a quantitative approach are only a few in Brazil (CARVALHO; CARRARO; The impact of brazilian clusters on local development: a propensity score matching approach SHIKIDA, 2016;JACOMETTI et al, 2016;ALDERETE;BACIC, 2016;ANTONIALLI, 2011;LEITE FILHO, 2010;BRITO et al, 2010;SANTOS, 2009). JACOMETTI et al (2016) analyses the impact of public policies on the economic development of the Arapongas, PR, furniture-focused APL.…”
Section: Local Development and Clustersmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are several studies on clusters impact evaluation on local development (MARINI; SILVA; NASCIMENTO, 2016; OLIVERIA; SANTANA, 2016; OLIVEIRA; MARTINELLI, 2014; MACEDO; DIAZ MERINO; DALLAZEN CAMILLO, 2014), most of them are case studies or qualitative studies. Studies based on a quantitative approach are only a few in Brazil (CARVALHO; CARRARO; The impact of brazilian clusters on local development: a propensity score matching approach SHIKIDA, 2016;JACOMETTI et al, 2016;ALDERETE;BACIC, 2016;ANTONIALLI, 2011;LEITE FILHO, 2010;BRITO et al, 2010;SANTOS, 2009). JACOMETTI et al (2016) analyses the impact of public policies on the economic development of the Arapongas, PR, furniture-focused APL.…”
Section: Local Development and Clustersmentioning
confidence: 99%
“…One of the main reasons is the presumed impact of clusters on firm performance, regional economic development, and country competitiveness. Several studies have stressed the positive impact of clusters on firm performance as enough evidence of their contribution to development CARRARO;SHIKIDA, 2016;KUKALIS, 2010;FOLTA;COOPER;BAIK, 2006;ROCHA, 2004;MASKELL;KEBIR 2004); by assuming that firm-level outcomes directly lead to regional or national outcomes. On the other side, only a few studies have identified a non-clear (and even negative) effect of clustering on productivity (DURANTON et al, 2011).…”
Section: Introductionmentioning
confidence: 99%